Une femme au gouvernement - Françoise Revaz; Stéphanie Pahud; Raphaël Baroni (Communication)
This paper aims to show how the events leading up to the election of a woman politician may have been structured as a soap opera by the daily press. It features an exemplary case of politics and celebrity journalism playing one upon another. It is the tension between the political agenda and the media agenda that creates and heightens the interest in the election, portrayed as a celebrity event.